Pond Water Quality Monitoring in Consumption Fish Farming Industry Based on Internet of Things - Subrata, Arsyad Cahya; Sulisworo, Dwi; Fitrianawati, Meita; Shafee Kalid, Khairul; Wan Ahmad, Wan Fatimah; Hamdi Batubara, Zul; Ramadhani, Muhammad (Universitas Trunojoyo Madura, 2024)
The rapid increase in population in Indonesia has increased the demand for animal protein. As a source of animal protein, fish has excellent potential to be developed in Indonesia. However, care for water quality, a basic need, is often ignored. Meanwhile, increasing fish production can be done by ensuring that water quality is always in good condition. This research conducted aims to monitor water quality continuously. Integrating water quality monitoring systems using the Internet of Things (IoT) offers convenience in real-time monitoring and does not have to be present on-site. The parameters determining fish water quality are pH, electrical conductivity (EC), dissolved oxygen (DO), turbidity, and water temperature. The data obtained is then displayed on the Water Monitoring dashboard as graphs, indicators, and raw data the user can download. Overall, the system can measure, monitor in real-time, and store data on the results of measuring the quality of freshwater fish ponds on smartphones/laptops. The developed system also provides information on whether the water quality is “normal” or in conditions less and more than the threshold. Therefore, the developed system helps farmers monitor the quality of their fish ponds to increase the productivity of fish farming.